2020
DOI: 10.1002/jgm.3276
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint mapping of a t(9;22;12) chronic myeloid leukaemia patient with e14a3 BCR‐ABL1 transcript using Nanopore sequencing

Abstract: BackgroundThe genetic changes in chronic myeloid leukaemia (CML) have been well established, although challenges persist in cases with rare fusion transcripts or complex variant translocations. Here, we present a CML patient with e14a3 BCR‐ABL1 transcript and t(9;22;12) variant Philadelphia (Ph) chromosome.MethodsCytogenetic analysis and fluorescence in situ hybridization (FISH) was performed to identify the chromosomal aberrations and gene fusions. Rare fusion transcript was verified by a reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In addition, we also reviewed the references of the retrieved literature. Currently, 62 cases with e14a3 (b3a3) transcripts were reported, including our present patient, of which 25 cases had relatively detailed information of the clinical characteristics and treatments ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Notably, male patients accounted for 84% (21/25) of the CML cases with the e14a3 (b3a3) transcript, which was consistent with previous studies [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also reviewed the references of the retrieved literature. Currently, 62 cases with e14a3 (b3a3) transcripts were reported, including our present patient, of which 25 cases had relatively detailed information of the clinical characteristics and treatments ( Table 2 ) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Notably, male patients accounted for 84% (21/25) of the CML cases with the e14a3 (b3a3) transcript, which was consistent with previous studies [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib, a potent inhibitor of the oncogenic tyrosine kinase BCR-ABL, has shown remarkable clinical activity in patients with CML [ 155 ]. Several studies have reported that PacBio sequencing and ONT sequencing can be applied to detect BCR-ABL1 fusion events and related tyrosine kinase inhibitor (TKI) resistance mutations in samples from CML patients both at diagnosis and during follow-up [ 156 ], [ 157 ], [ 158 ]. These technologies are also important for identifying other components involved in CML pathogenesis to can be exploited to overcome tyrosine kinase inhibitors (TKI) resistance.…”
Section: Applications Of Tgs Technologies In Cancermentioning
confidence: 99%
“…Chronic myeloid leukaemia (CML), a subtype of myeloproliferative neoplasm (MPN), is characterized by the translocation t(9;22)(q34;q11), the Philadelphia (Ph) chromosome [1]. The resulting breakpoint cluster region (BCR)::Abelson (ABL) chimeric protein which stimulates high levels of protein kinase activity is a hallmark of the leukemogenesis in CML patients [2,3].…”
Section: Introductionmentioning
confidence: 99%